The birth of architectural modernism from the spirit of antiquity - Zavadovsky, Petr (project baikal, 2021)
The article focuses on the role of antiquity in general and the Athenian Acropolis in particular in the formation of Le Corbusier’s creative individuality and the key subjects and ideas of his works.
Keywords: Le Corbusier; modernism; antiquity; Acropolis; Parthenon; F. Nietzsche